Disruptive technologies in the university curriculum: use of artificial intelligence - Reeves Huapaya, Enma Sofía; Lazo Chucos, Gilmer; Parillo Sosa, Efrain; Meza, Melva Iparraguirre (Institute of Advanced Engineering and Science, 2025)
The so-called “digital era” is synonymous with the transformation of every aspect of human life. This transformation is given by the development of new technologies that modify the way humans communicate and cooperate. Now, it can be said that formal education, compared to other economic sectors, is lagging in the integration of novel technologies in higher education curricula, especially in terms of implementing artificial intelligence (AI). The objective of this research was to conduct a systematic review of the scientific production related to the incorporation of artificial intelligence as a disruptive technology in the university curriculum. It was carried out using a qualitative approach based on a systematic review. The review showed a greater scientific production between 2022 and 2023; it was also evidenced that, as a technology, artificial intelligence has become a disruptive element thanks to its ability to change the role and work performed by teachers, students, and educational institutions. Consequently, the university of the future urgently needs to plan, design, develop, and implement curricula that include artificial intelligence, with the purpose of training better professionals, capable of acting effectively in a technological and productive environment.